(untitled) (Tribhuvan University Journal of Microbiology, 2019)
Objectives: To isolate methicillin resistant Staphylococcus aureus (MRSA) from anterior nares of dairy workers and dairy products and assess the antibiotic susceptibility pattern of the isolates. Methods: Swab samples collected from anterior nares of dairy workers and dairy product (butter) were inoculated into mannitol salt agar and incubated at 37ºC for 24 hours. Identification was done based on colony characteristics, Gram’s staining, catalase, oxidase and coagulase test. Antibiotic susceptibility testing was done by modified Kirby Bauer disc diffusion method. MRSA was confirmed by using cefoxitin disc. Results: A total of 109 S. aureus (98 from dairy workers and 11 from butter samples) were isolated. Out of them 32 MRSA were isolated from dairy workers and 4 from butter samples. The association between age group and MRSA was found insignificant (p = 0.115). The association of MRSA between male and female workers was found significant (>0.05). About 86% of the MRSA isolates were susceptible to Gentamicin (86.11%) followed by Ciprofloxacin (77.78%). Conclusion: Detection of MRSA among dairy workers and dairy products warrants proper handling and adequate control measures to prevent transmission of MRSA from dairy industry.